SOCIAL AND PEDAGOGICAL ACTIVITIES OF MAKHMUDKHOJI BEHBUDI IN SOLVING THE MAIN PROBLEMS OF THE DEVELOPMENT OF PROCESSES OF SPIRITUAL AND MORAL EDUCATION - Axrarova Zebuniso (Galaxy International Interdisciplinary Research Journal, 2023)
Today, the study of the views of great educators on the harmonious education of the younger generation, an objective assessment of the history of pedagogical teachings, in particular, the spiritual and moral views and creativity of the Jadidist movement in Turkestan and its major figure Mahmudhodji Behbudi, also becomes relevant. The article discusses the mechanisms of using the spiritual and moral views of the great educator in the processes of education of a higher educational organization.